PENGARUH ETHNOSENTRISME KONSUMEN TERHADAP KETERLIBATAN PENGAMBILAN KEPUTUSAN PEMBELIAN PRODUK - Dewi Fadila; Nirwan Rasyid (Politeknik Negeri Sriwijaya, 2012)
The objective of this study was to determine consumer ethnocentrisme in Palembang. Ethnocentrism defined as the tendency of consumers to accept or reject any foreign-made products. Ethnocentrism is considered as an effortt better understand consumer behavior related to affective and normative aspect to buy national product. CETSCALE, ethnocentrisme scale consumers from Shrimp & Sharma used in this study. Data collection used a questionnare with seven points of measurement Likert Scale. A convinience sample of 90 students was employed in this study. The Spearman test apply to the correlation of consumer ethnocentrisme and low involvement also high involvement decission process. The result conclude that consumers have a low preference to use of local product, among low invelvement and high involvement decission process. Indonesian government and companies need to increasing consumers awereness to use local product.